Recent insights on CME deflections at low heights - Cécere, M.; Costa, A.; Cremades, H.; Stenborg, G. (Frontiers in Astronomy and Space Sciences, 2023)
It has been shown that the magnetic structures surrounding coronal mass ejection (CME) events play a crucial role in their development and evolution along the first few solar radii. In particular, active regions, coronal holes, pseudostreamers, and helmet streamers are among the main coronal structures involved in the deviation of the trajectory of CMEs from their radial direction. Therefore, comprehensive observational studies along with their theoretical interpretation, aided by numerical simulations of the early evolution of CMEs, are the key ingredients to help determine their 3D trajectory in the interplanetary medium to narrow down the error in the estimation of the time of arrival of geoeffective events. In this mini-review, we compile the last decade of theoretical, numerical, and observational research that has shed light on the causes influencing the early deflection of CMEs away from their otherwise radial trajectory.